REVITALISASI MANTRA DEBUS: PENGUATAN KEARIFAN LOKAL SEBAGAI BAHAN AJAR SASTRA DI SD - Syah, Ezik Firman; Agustina, Noni; Damayantie, Irma (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Primary school teachers ignore the local wisom when teaching Indonesian literature. They also have much interdependence of using textbooks. The study aims to explore the revitalization of debus mantra as the alternative learning material to foster local wisdom in elementary school level. The research method employed was qualitative ethnography. Field observation, interview and documentation protocol sheets were used to collect the data. The data were collected at Surya Galung community, Serang, Banten, Indonesia. Result suggested that debus mantra could be used as the alternative learning material to teach Indonesian literature in elementary school level because it can withstand external cultures, accommodates elements of external cultures, integrates components of external cultures into the native culture, and privides the direction for cultural progress.